Development of cell oedema in piglet hearts during ischaemia monitored by dielectric spectroscopy - Lück, Sabrina; Preusse, Claus-Jürgen; Delis, Achilles; Schäfer, Michael (Bioelectrochemistry, 2019)
Objective: The aim of this research was to investigate if dielectric spectroscopy between 100Hz and 1MHz provides reliable information about water distribution in ischaemic heart tissue and to investigate the influence of temperature on oedema formation. Methods: We examined hearts of landrace piglets (n=13) during ischaemia at 35°C, 25°C, and 15°C. The dielectric permittivity ε’(f) and conductivity σ‘(f) were calculated from impedance spectra measured between 100Hz and 1MHz. Gap junction uncoupling (GJU) was identified in the sigmoidal time course of ε’(13kHz). The extracellular space index (ECSI) was estimated by the ratio σ‘(100Hz)/σ‘(1MHz). Intercalated water was analysed in electron microscopy images of the myocardial samples and was used to calculate the extracellular space index ECSIhisto. The ECSI and ECSIhisto were compared during ischaemia. GJU and oedema formation were simulated with an electrical heart model. Results: At the onset of ischaemia, the ECSI was significantly higher than the ECSIhisto (p<.01). GJU during ischaemia was temperature-dependent. After GJU, the values of the ECSI and ECSIhisto matched very well. The simulations confirmed the influence of GJU on the ECSI. Significance: The estimation of cell oedema with the ECSI is reliable only after GJU. The development of oedema estimated by the ECSI was delayed at cooler temperatures.